Rape cases among the Malays in Kuala Lumpur : a textual analysis of police reports and statements from the year 2006 to 2009 - Bazlin Darina Ahmad Tajudin (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2011)
This study discusses rape cases among the Malays in Malaysia, particularly in Kuala Lumpur. It was conducted at the Kuala Lumpur Contingent Police Headquarter (IPK, KL) involving 45 rape cases based on police reports and statements from the year 2006 to 2009. The study classifies these 45 cases into two categories, namely, 40% (18 cases) statutory rape cases and 60% (27 cases) non-statutory rape cases. Statutory rape is defined as having sexual intercourse with or without consent with a girl who is under the age of 16 years old whereas, non-statutory rape means having forced sexual intercourse involving individuals above the age of 16 years old. The study shows that in statutory rape cases, the majority of the victims engaged in dating relationship with adult perpetrators. As for non-statutory rape cases, five types of rape were discovered: date rape, acquaintance rape, gang rape, stranger rape and OKU (Orang Kelainan Upaya) rape. Several important findings were discovered throughout the study, of which there are certain factors that contribute to statutory and non-statutory rape incidences. These include trust and naivety, lepak (loafing), family and poor religious awareness. It is also interesting to state that coupling at a young age is considered the main contributing factor to statutory rape incidences, while, time and location as well as pornography also serve as factors for non-statutory rape cases. Using an integrated approach of the victims and perpetrators' statements, the study is thoroughly able to describe and differentiate the forms of consent and non-consent behaviours portrayed by the victims and the perpetrators. In this study, it is found that the issue of consent is more imminent in non-statutory rape compared to statutory rape cases. Having the use of textual analysis as a methodology in rape research enables this study to elicit massive information about rape from police reports and statements of various viewpoints. Finally, this study suggests that it is pertinent to have sex education particularly on one's sexuality in order for individuals to behave accordingly with the opposite sex. What is more important is the emphasis on Islamic framework in addressing issues surrounding sexuality. In addition, this study also proposes that continuous campaigns and prevention programmes on the importance of parenting, self-preservation and implications of social misconduct should be further emphasized.